Al-Qur’an : Reading For Reality: (Membaca al-Qur’an ‘ala Ahmad an-Na’im) - Ahmad Khamid (Al Irfani: Journal of Al Qur'anic and Tafsir, 2022)
Islamic thought was born to answer the anxiety over the reality faced by an intellectual. Ahmad an-Na'im is a figure who arises from the unease over the reality of Muslims in disciperizing the concept of shari'ah and the state. This article uses explorative analysis, an-Na'im ideas about the Qur'an will be the focus of the study. The Qur'ān guides human behavior and morality, it is not a textual narrative about the law. This became the paradigm of the Qur'an, the Qur'an as reading for reality. The conception of the Qur'an in view of the reality of makki-madani makes the terma nask-mansukk not abolition, but a temporary delay in the implementation of verses. Aspects of makkiyah verse can be postponed and replaced with aspects in the verse madaniyah. The Qur'an is not a book that because of its contradiction makes people lazy to think.